1999
DOI: 10.1128/mmbr.63.1.54-105.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42: An Essential Rho-Type GTPase Controlling Eukaryotic Cell Polarity

Abstract: SUMMARY Cdc42p is an essential GTPase that belongs to the Rho/Rac subfamily of Ras-like GTPases. These proteins act as molecular switches by responding to exogenous and/or endogenous signals and relaying those signals to activate downstream components of a biological pathway. The 11 current members ofthe Cdc42p family display between 75 and 100% amino acid identity and are functional as well as structural homologs. Cdc42p transduces signals to the actin cytoskeleton to initiate and maintain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
263
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(269 citation statements)
references
References 657 publications
(819 reference statements)
3
263
0
3
Order By: Relevance
“…Moreover, it has been shown that Bag7p overproduction suppresses the cold sensitivity of a sac7 strain [13]. The Lrg1 protein seems to play a role during the mating process in yeast [34], and Cdc42p has also been shown to act during mating projection formation [35]; these data indicate that the interaction between Lrg1p and Cdc42p is signi¢cant. Rgd2p interacts with the Cdc42p and Rho5p.…”
Section: Bag7p Lrg1p and Rgd2p Physically Interact With Speci¢cmentioning
confidence: 99%
“…Moreover, it has been shown that Bag7p overproduction suppresses the cold sensitivity of a sac7 strain [13]. The Lrg1 protein seems to play a role during the mating process in yeast [34], and Cdc42p has also been shown to act during mating projection formation [35]; these data indicate that the interaction between Lrg1p and Cdc42p is signi¢cant. Rgd2p interacts with the Cdc42p and Rho5p.…”
Section: Bag7p Lrg1p and Rgd2p Physically Interact With Speci¢cmentioning
confidence: 99%
“…The Ile-46 to Met (I46M) substitution in Cdc42 inhibits the binding between Cdc42 and the Ste50 RA domain, and cdc42-I46M mutant cells are defective in the FG response (Mösch et al, 2001;Truckses et al, 2006). The positions of Leu-4 and Ile-46 are far from the GTP binding/hydrolysis domains and the effector binding regions called Switch I (residues 26-40) and Switch II (residues 58-76) (Johnson, 1999). It is therefore likely that Cdc42 binds to the Ste50 RA domain and to the Ste20/Cla4 CRIB domain via different regions of the molecule.…”
Section: Interaction Between Cdc42 and Ste50mentioning
confidence: 99%
“…cells, Cdc42 has been implicated in the regulation of an actin rearrangement, receptor-mediated signal transduction pathways, cell cycle progression, apoptosis and multiple membrane trafficking events, including phagocytosis, exocytosis, and endocytosis. Cdc42 may also govern pathways required for establishment and maintenance of cellular polarity [49]. Expression of skeletal muscle a-actin (a-SMA) and thymosin b-10 (TB-10)-the intracellular matrix related genes-was strongly inhibited at 6 h by 1,25-(OH) 2 D 3 ( Table 4).…”
Section: 25-(oh) 2 D 3 Target Genes Of Transporters and Channelsmentioning
confidence: 99%